Electrical and optical properties of fluorine-doped tin oxide (SnOx:F) thin films deposited on PET by using ECR-MOCVD - Park, Ji Hun; Byun, Dong Jin; Lee, Joong Kee (SPRINGER, 2009)
The electrical, optical, structural and chemical bonding properties of fluorine-doped tin oxide (SnOx:F) films deposited on a plastic substrate prepared by Electron Cyclotron Resonance-Metal Organic Chemical Vapor Deposition (ECR-MOCVD) were investigated with special attention to the process parameters such as the H-2/TMT mole ratio, deposition time and amount of fluorine-doping. The four point probe method, UV visible spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic emission spectroscopy (AES), X-Ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were employed to characterize the films. Based on our experimental results, the characteristics of the SnOx:F thin films were significantly affected by the process parameters mentioned above. The amount of fluorine doping was found to be one of the major parameters affecting the surface resistivity, however its excess doping into SnO2 lead to a sharp increase in the surface resistivity. The average transmittance decreased with increasing film thickness. The lowest electrical resistivity of 5.0 x 10(-3) a"broken vertical bar(.)cm and highest optical transmittance of 90% in the visible wavelength range from 380 to700 nm were observed at an H-2/TMT mole ratio of 1.25, fluorine-doping amount of 1.3 wt.%, and deposition time of 30 min. From the XRD analysis, we found that the SnOx:F films were oriented along the (2 1 1) plane with a tetragonal and polycrystalline structure having the lattice constants, a = 0.4749 and c = 0.3198 nm.
Keywords: CHEMICAL VAPOR-DEPOSITION; SOLAR-CELLS; PHOTOVOLTAICS; HISTORY